Discharge and infection in retinoblastoma post-enucleation sockets - Mourits DL (Dove Medical Press, 2017)
Daphne L Mourits,1 Dyonne T Hartong,1 Andries E Budding,2 Machteld I Bosscha,1 H Stevie Tan,1 Annette C Moll1 1Department of Ophthalmology, VU University Medical Center, 2Department of Microbiology, Academic Medical Center, Amsterdam, the Netherlands Purpose: To investigate the causes and treatment options for socket discharge and infection in patients enucleated for retinoblastoma (Rb). Methods: A questionnaire was filled out by (parents of) ocular prosthesis-wearing patients with a history of enucleation as treatment for Rb. We collected data on patients’ characteristics, cleaning habits of the prosthesis, frequency of socket irritation, discharge, and infection, and use of antibiotics. With ordinal logistic regression analysis, factors related to the outcome parameters (frequency of irritation, mucoid and purulent discharge) were identified. In a subset of young asymptomatic and symptomatic patients, a swab culture of the socket was performed to determine the presence of microorganisms. Results: A total of 186 patients or their parents (mean age of the patients: 17.3 years, ranging from 0.8 to 88.3 years) filled out the questionnaire. Irritation, mucoid discharge, and purulent discharge were frequently (once a month or more often) experienced in 75 (39.5%), 127 (66.8%), and 15 (13.2%) sockets, respectively. Younger age was associated with a higher frequency of mucoid and purulent discharge. Radiation therapy, chemotherapy, gender, age at surgery, cleaning frequency, and nocturnal wear were not associated with the outcome parameters. In a subgroup of 26 patients, the sockets were swabbed and cultured. All symptomatic patients had a positive bacterial culture versus 15% (2/13) of the asymptomatic patients (P<0.001). Common cold was correlated with both symptoms and presence of bacteria. Haemophilus influenzae and Staphylococcus aureus were the species most frequently cultured. Conclusion: Ocular prosthesis-wearing patients often experienced mucoid discharge, and less often irritation and socket infection. These complaints were found to decrease with increasing age, but did not seem to be influenced by cleaning or wearing habits. Symptomatic sockets, with and without discharge, were correlated with the presence of pathogenic bacteria for which local antibiotic treatment seemed effective in most cases. Keywords: microorganisms, inflammation, prosthesis, cleaning habits